2022
DOI: 10.3389/fmicb.2022.875485
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antiviral Activity of Ethyl 3-Hydroxyhexanoate Against Coxsackievirus B Infection

Abstract: Coxsackievirus group B (CVB) is a member of the genus Enterovirus in the family Picornaviridae. CVB infection has been implicated as a major etiologic agent of viral myocarditis, dilated cardiomyopathy, meningitis, and pancreatitis among children and young adults. Until date, no antiviral agent has been licensed for the treatment of Coxsackievirus infection. In an effort to identify antiviral agents against diseases caused by the CVB, we found that ethyl 3-hydroxyhexanoate (EHX), a volatile compound present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Ethyl 3hydroxyhexanoate (EHX) is a fatty acid ethyl ester of 3hydroxyhexanoic acid, which is a key volatile compound in several fruits and is a potent antiviral compound (Medina et al, 2020). Olasunkanmi et al (2022) demonstrated that EHX treatment significantly inhibits CVB replication both in vivo and in vitro.…”
Section: Treatmentmentioning
confidence: 99%
“…Ethyl 3hydroxyhexanoate (EHX) is a fatty acid ethyl ester of 3hydroxyhexanoic acid, which is a key volatile compound in several fruits and is a potent antiviral compound (Medina et al, 2020). Olasunkanmi et al (2022) demonstrated that EHX treatment significantly inhibits CVB replication both in vivo and in vitro.…”
Section: Treatmentmentioning
confidence: 99%